Job turnover among workers in giant hypermarket Plentong / Rozana Othman - Othman, Rozana (Faculty of Business and Management, 2009)
Using insights from the relevant literature and recent empirical data, this research investigates the job turnover in Retail Company in the case of GCH Retail (M) Sdn Bhd or well known as Giant Hypermarket in Plentong, Johor Bahru. This research proposes a mechanism of the determinants the job turnover in Giant Hypermarket Plentong which translates into individual decisions to quit. The strongest factors that bring to job turnover in Giant Hypermarket Plentong were identified which are external business environment, job satisfaction and role conflict. With all this factors, Giant Hypermarket Plentong will continuously facing increasing in job turnover and the number of turnovers is creating fear. Descriptive research is used in designing this research. Secondary data and primary data are used for the study. The turnover situation in Giant Hypermarket Plentong is being observed and 60 questionnaires are being distributed to the staff as respondent in order to gain the real opinion of the job turnover situation in this company. Furthermore, Exit Interview data also was collected and 20 staff have been interviewing to support the ideas of job turnover from resigned workers and illustrated the real causes or factors that lead to job turnover in Giant Hypermarket Plentong. This finding focuses on whether the all determinants are really impact on job turnover towards Giant Hypermarket Plentong. From the analysis, Giant Hypermarket Plentong can reduce the problem by do some modification on their company management by providing more comfortable workplace for their staff and also improve the work facilities in order to cope with new technology revolution and other competitors to make the workers stay longer in this company. In addition, Giant Hypermarket Plentong also should improve the quality standard of working environment and the level of job satisfaction among workers to ensure the job turnover problem in Giant Hypermarket Plentong will reduce more into safety level. Furthermore, revision by Human Resource team on Salary and benefit package that have been given to their staff also need to be done by improving the package to attract their workers become loyal and stay more longer with this company. This research also illustrates the importance for managers understand the extent to which turnover decisions can be prevented. Hopefully, it helps the company to improve their performance in futures.